#TITLE_ALTERNATIVE# - NURADNAN PRAMUDITA (NIM 10303013), ALMA
HERSCHEL is the fourth cornerstone mission from long-term ESAÃƒÂ‚Ã‚Â’s program ÃƒÂƒÃ‚ÂƒÃƒÂ‚Ã‚Â‚ÃƒÂƒÃ‚Â‚ÃƒÂ‚Ã‚Â“Horizon 2000ÃƒÂ‚Ã‚Â” (following Cluster II, XMM, and Rosetta). It is designed to observe electromagnetic signal in submillimeter and long-infrared, with wavelength coverage of 57-670 μm. Exploration of this wavelength domain is very few compared to radio, nearinfrared, or optical domain. The concept of HERSCHEL includes a Cassegrain telescope with 3.5 m telescope, f/9.8, cooled at operational temperature of 80 K. This cooling is made possible using liquid helium cryostat. HERSCHEL will be placed at about Sun-Earth Lagrange L2 for about 4.5 years. There are some advantages from the concept of HERSCHEL. First, for some ranges of frequency, high sensitivity will be achieved. Second, the placement of HERSCHEL guarantees wide observation field and long observation time. Third, due to the virtually empty space, the data taken will be unobstructed by atmospheric absorption profiles. One of the scientific objectives of HERSCHEL mission is molecular study. This is because at HERSCHELÃƒÂ‚Ã‚Â’s wavelength coverage, there are so many spectral line from molecular rotational transition. In this Final Project, the potential of HERSCHEL in the study of NeptuneÃƒÂ‚Ã‚Â’s atmosphere will be explored. Observations of Neptune itself are not very exhaustive compared to those for Jupiter, Saturn, or Titan. After the completion of this work, only Voyager 2 has visited Neptune, during flyby at 1989. So far no mission specially dedicated to study Neptune is planned. Among Jovian planets, Neptune, together with Uranus, is grouped as ÃƒÂ‚Ã‚Â“ice giantÃƒÂ‚Ã‚Â”, differing from Jupiter and Saturn which are ÃƒÂ‚Ã‚Â“gas giantsÃƒÂ‚Ã‚Â”. This difference is due to the larger heavy elements abundance in Neptune. From study at HERSCHELÃƒÂ‚Ã‚Â’s wavelength domain, models of many photochemical reactions could be confirmed, or rejected, and new discoveries is highly probable. Finally, study of outer planets could constrain various aspects of the Solar System formation model, and planetary system in general. Here, spectrograms of some molecules will be presented. Analysis of signal intensity and noise level will also be given. These two parameters are required to determine the signal-to-noise value, or S/N. This S/N is the indicator of value for an observation. Identification of molecules requires appropriate resolution. In the case of NeptuneÃƒÂ‚Ã‚Â’s atmosphere, spectral resolutions given by HIFI is the only appropriate ones. Because of that, analysis will be done only for spectrograms generated using parameters of HIFI. Other than that, in order to increase the efficiency of observation, selection of wavelength interval will be chosen carefully, considering the bandwidth provided by HIFI.